To subtract \(2x\) from both sides of the two equations, you start with:
- \(y = -6 + 2x\)
- \(y = 2x - 4\)
Now, let's rewrite the equations by subtracting \(2x\) from both sides.
For the first equation:
Starting with: \[ y = -6 + 2x \] Subtract \(2x\) from both sides: \[ y - 2x = -6 \] So, you can write it as: \[ -y + 2x + y = -6 \]
For the second equation:
Starting with: \[ y = 2x - 4 \] Subtract \(2x\) from both sides: \[ y - 2x = -4 \] So it can be rewritten as: \[ -y + 2x + y = -4 \]
Final rewritten equations:
- \(y - 2x = -6\)
- \(y - 2x = -4\)
Thus, the results of subtracting \(2x\) from both sides of the equations are:
- \(y - 2x = -6\)
- \(y - 2x = -4\)